Risk and Efficiency in East Asian Banks - Laeven, Luc 1999- (The World Bank, 1999)
Banks restructured after East Asia's crisis of 1997 - most of them family-owned or company-owned and almost never foreign-owned - tended to be heavy risk takers. Most of them had excessive credit growth. - Laeven uses a linear programming technique (data envelopment analysis) to estimate the inefficiencies of banks in Indonesia, the Republic of Korea, Malaysia, the Philippines, and Thailand. He applies this technique to the precrisis period 1992-96. Assessing a bank's overall performance requires assessing both efficiency and risk factors, so Laeven also introduces a measure of risk taking. This risk measure helps predict which banks were restructured after the crisis of 1997. Laeven finds that foreign-owned banks took little risk relative to other banks in East Asia, and that family-owned and company-owned banks were among the highest risk takers. Banks restructured after the 1997 crisis had excessive credit growth, were mostly family-owned or company-owned, and were almost never foreign-owned. This paper - a product of the Financial Sector Strategy and Policy Department - is part of a larger effort in the department to study the causes and resolution of financial distress. The author may be contacted at llaeven@worldbank.org